2019
DOI: 10.1111/pde.13888
|View full text |Cite
|
Sign up to set email alerts
|

Apple cider vinegar soaks [0.5%] as a treatment for atopic dermatitis do not improve skin barrier integrity

Abstract: Background/Objectives Atopic dermatitis (AD) is a common chronic inflammatory skin condition associated with high transepidermal water loss, high skin pH, and Staphylococcus aureus skin colonization. The treatment of AD with bath additives remains highly debated. Recent evidence suggests that dilute apple cider vinegar (ACV) may improve skin barrier integrity in AD, but its safety and efficacy are not well studied. This pilot split‐arm study analyzed the effect of dilute apple cider vinegar soaks on skin barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…As previously described, skin pH cannot be easily altered sustainably by the study emollients although a short‐term change was observed (Figure ) 9,44 . However, especially in AD, a temporary difference in skin pH was observed, hinting toward a reduced buffer capacity in AD.…”
Section: Discussionmentioning
confidence: 57%
“…As previously described, skin pH cannot be easily altered sustainably by the study emollients although a short‐term change was observed (Figure ) 9,44 . However, especially in AD, a temporary difference in skin pH was observed, hinting toward a reduced buffer capacity in AD.…”
Section: Discussionmentioning
confidence: 57%
“…Another study reported that 0.5% acetic acid daily bath for 14 days did not improve skin barrier function or acidity in patients with AD, as compared with plain water baths. 53 In contrast, skin irritation was reported in some patients treated with dilute acetic acid. Chlorhexidine bath has been used in the decolonization of MRSA in the general population, but it has not been studied adequately in AD.…”
Section: Prevention Of Infections In Admentioning
confidence: 99%
“…43 Patients with atopic dermatitis showed a significantly lessened skin tolerance for acetic acid and higher incidence of irritant reactions. 28,43 Chemical burns: partial or complete thickness burns have been reported on application of glacial acetic acid or undiluted acetic acid. 5 Vaginal burns, bleeding and blistering if accidently high concentration is applied.…”
Section: Cutaneous Adverse Effects Of Acetic Acidmentioning
confidence: 99%